Revealing the Mechanism behind the Catastrophic Failure of n‐i‐p Type Perovskite Solar Cells under Operating Conditions and How to Suppress It. (8th July 2021) - Ding, Changzeng; Yin, Li; Zhang, Lianping; Huang, Rong; Fan, Shizhao; Luo, Qun; Lin, Jian; Li, Fangsen; Zhao, Chun; Österbacka, Ronald; Ma, Chang‐Qi
Abstract: The n‐i‐p type perovskite solar cells suffer unpredictable catastrophic failure under operation, which is a barrier for their commercialization. The fluorescence enhancement at Ag electrode edge and performance recovery after cutting the Ag electrode edge off prove that the shunting position is mainly located at the edge of device. Surface morphology and elemental analyses prove the corrosion of the Ag electrode and the diffusion of Ag + ions on the edge for aged cells. Moreover, much condensed and larger Ag clusters are formed on the MoO3 layer. Such a contrast is also observed while comparing the central and the edge of the Ag/Spiro‐OMeTAD film. Hence, the catastrophic failure mechanism can be concluded as photon‐induced decomposition of the perovskite film and release reactive iodide species, which diffuse and react with the loose Ag clusters on the edge of the cell. The corrosion of the Ag electrode and the migration of Ag + ions into Spiro‐OMeTAD and perovskite films lead to the forming of conducting filament that shunts the cell. The more condensed Ag cluster on the MoO3 surface as well as the blocking of holes within the Spiro‐OMeTAD/MoO3 interface successfully prevent the oxidation of Ag electrode and suppress the catastrophic failure. Abstract : The catastrophic failure of n‐i‐p type perovskite solar cells under operation is reported, which is proven by the corrosion of the metal electrode on the edge. After inserting a thin MoO3, the improved Ag thin film morphology as well as better energy alignment suppress the catastrophic failure of perovskite solar cells.